Decreased Employee Work Motivation during a Pandemic in CV. Artez Cipta Gemilang Bandung - Sofyandi, Herman; Hapsari, Ayuningtyas Y.; Ramadhan, Nabilah; Oktafien, Shinta; Agustriyana, Darwis (CENTRAL ASIA AND THE CAUCASUS, 2022)
Motivation is a self-motivation from someone that causes distributes and supports in achieving optimal goals. Every company with compensation must be able to motivate appropriately. The purpose of our research is to analyze the decreased of work motivation employee at CV. Artez Cipta Gemilang. All sectors of the business industry experienced a very significant decline, decreased sales levels, consumers also delayed work, to operational costs that must be carried out normally by minimizing income. So like it or not, the company has to reduce the number of employees. Companies need to find more appropriate solutions to solve this problem, so that employees are able to improve their work performance again. Because this is allowed to disrupt all company activities so that the company will experience losses. The theory that we use in this research is Motivation Theory by Mc Cleland’s which we analyze in detail. Using a descriptive method, we use a theory regarding employee motivation, then we analyze it by collecting data in the field so that we can conclude and give the best advice for CV. Artez Cipta Gemilang.